Effect of thermal and dry salt-curing processing on free and bound phenolics and antioxidant activity in Prunus mume fruits together with the phenolic bioaccessibility. (June 2021) - You, Bangyan; Yang, Shiying; Yu, Jiawen; Xian, Wenyan; Deng, Yu; Huang, Wei; Li, Wu; Yang, Ruili
Abstract: Thermal and dry salt-curing processing are traditional methods for processing Prunus mume fruits (PMF) into food or medicine. This study aimed to investigate the composition of free and bound phenolics in PMF, and effects of thermal and dry salt-curing processing on phenolic profiles, antioxidant activity and bioaccessibility. Nineteen (free and bound) phenolic compounds were identified and quantified in raw PMF. Salt-curing caused a significant decrease in free and bound phenolic content, whereas no significant change was observed after thermal treatment. The concentration and distribution of individual phenolic compounds instead of composition in PMF were changed by thermal and salt-curing processing. The two processing methods diﬀerently decreased DPPH and ABTS antioxidant activity. The total phenolic bioaccessibility increased by 34.09% after thermal processing, while decreased by 87.92% after salt-curing. These results may indicate that thermal rather than salt-curing is more preferably method for processing PMF to developing health foods and nutraceuticals. Highlights: The bound phenolics in P. mume fruits were firstly identified and quantitated. Thermal and salt-curing processing changed phenolics content and distribution. The two processing methods diﬀerently decreased antioxidant activity of P. mume . Phenolic bioaccessibility of FM increased compared with that of PMF and SPM. Thermal treatment was more effective in preserving phenolics compared to salt-curing.